Pengaruh Kompetensi, Pelatihan dan Pengembangan SDM terhadap Kinerja Pegawai (Studi Kasus Pada Pegawai SMKN 3 Jombang) - Mufidatul A'yun; Lailatus Sa’adah (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The purpose of this study is to examine how employee performance at SMKN 3 Jombang is affected by competency, training, and human resource development (HRD). To investigate the connections between the variables, the study uses a quantitative method using an associative approach. Of the 161 employees in the study population, 113 were chosen as the sample. The findings indicate that competency, training, and HR development have a positive and significant effect on employee performance, both partially as shown through the t-test and simultaneously through the F-test. These results suggest that improving the quality of human resources through strengthening knowledge, understanding, technical skills, and hands-on training supports the optimization of work quantity, work quality, and employee collaboration in carrying out educational duties. The study recommends that SMKN 3 Jombang implement an integrated HR development system based on needs analysis, focusing on enhancing digital competencies, fostering adaptive personality traits, and creating a motivating work environment to ensure sustainable performance improvement.